The recent microapartments in São Paulo: A case study of thermal and luminous performance - Leme , Carolina Carvalho; Monteiro , Leonardo M.; Gonçalves , Joana C. S. (Seven Editora, 2023)
The compact apartments in the city of São Paulo have been growing significantly since 2013, driven by the economic, social, urban and demographic transformations of the recent decades. In 2021, the micro-apartments with less than 45m² accounted for 76% of the total residential launches in the city of São Paulo, with 58% between 45m² and 30m². The high representation of micro-apartments in the current real estate situation in São Paulo emphasizes the importance of studies focused on these new housing models. The objective of the article is to verify the thermal and luminous performance of open-plan micro-apartments produced between 2011 and 2017 in the city of São Paulo. The method is experimental based on empirical surveys of thermal and light variables from five case studies. The measurement results were comparatively analyzed from design and environmental assessments, allowing to investigate issues related to the thermal and luminous comfort of the user of the case studies. The results indicated the low environmental quality of the evaluated micro-apartments, with at least 45% of the time in cold discomfort during the winter and only 60% of IDU in the year (useful daylight illuminances: 300lux –3000lux). DOI:https://doi.org/10.56238/alookdevelopv1-125